2007
DOI: 10.3310/hta11140
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and economic evaluation of statins for the prevention of coronary events

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
316
2
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(331 citation statements)
references
References 301 publications
(289 reference statements)
4
316
2
9
Order By: Relevance
“…Instead, as with assigning first CVD events, the statin HTA reports the probability of future events, conditional on the nature of the previous event. 287 More details on the probabilities within a year of transitioning from stable angina, unstable angina, MI, TIA or stroke for individuals in different age groups can be found in an online discussion paper. 263 DOI: 10.3310/pgfar05110 PROGRAMME GRANTS FOR APPLIED RESEARCH 2017 VOL.…”
Section: Exploratory Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, as with assigning first CVD events, the statin HTA reports the probability of future events, conditional on the nature of the previous event. 287 More details on the probabilities within a year of transitioning from stable angina, unstable angina, MI, TIA or stroke for individuals in different age groups can be found in an online discussion paper. 263 DOI: 10.3310/pgfar05110 PROGRAMME GRANTS FOR APPLIED RESEARCH 2017 VOL.…”
Section: Exploratory Analysismentioning
confidence: 99%
“…An absolute decrement of 0.004 per year is applied in the model; this is based on previous HTA modelling in CVD. 287 Body mass index and utility…”
Section: Baseline Utilitymentioning
confidence: 99%
See 1 more Smart Citation
“…43 The relationship between age and utility was described as follows: utility = 1.060-0.004 × age. 44 After a CVE, patients in the model incurred a disutility, based on data of the Dutch national burden of disease study. [45][46][47] After an MI or stroke, the disutility was 0.288 and 0.609, respectively.…”
Section: Costsmentioning
confidence: 99%
“…In cost-effectiveness analyses the costs and health effects of an intervention are compared to determine whether the intervention provides value-for-money (Morris et al, 2007). Statins have been assessed for cost-effectiveness in a range of publications (for review see Franco et al (2005) and Gumbs et al (2007)), and were found to be cost-effective for high risk patients (Franco et al, 2005;Ward et al, 2007). In contrast, to date only two studies evaluated the cost-effectiveness of phytosterols or -stanols (Gerber et al, 2006;Martikainen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%